Correlates to seroprevalent herpes simplex virus type 2 among rural Appalachian drug users. Issue 3 (27th August 2015) - Stephens, Dustin B.; Young, April M.; Mullins, Ursula L.; Havens, Jennifer R.
Abstract : Herpes simplex virus type 2 (HSV‐2) is the most common cause of genital ulcer disease and, along with substance abuse, an important HIV risk factor. Therefore, the purpose of this study was to examine HSV‐2 seroprevalence in a sample of drug users in rural Appalachia. Rural Appalachian individuals age 18 or older reporting non‐medical use of prescription opioids, heroin, crack/cocaine, or methamphetamine in the past 6 months (n = 499) were included. Behavioral, demographic, and sexual network data were collected using interviewer‐administered questionnaires. Participants' serum was tested for HSV‐2 antibodies using the Biokit rapid test (Lexington, MA). The estimated population seroprevalence of HSV‐2 was 14.4% (95%CI: 9.6–19.4%). Only 8.8% were aware of being HSV‐2+, and unprotected sex was reported in 80% of serodiscordant sexual relationships. In a multivariate model, female gender, age, older age at first oral sex, and frequency of unprotected sex in the sexual network were independently associated with HSV‐2 seropositivity. Despite lower seroprevalence than that reported in similar studies of substance abusers, targeted interventions to reduce sexual risk behavior are warranted in this underserved population. Network‐informed approaches with particular focus on women, older individuals, and those engaging in frequent unprotected sex are recommended. J. Med. Virol. 88:512–520, 2016 . © 2015 Wiley Periodicals, Inc.